An analysis of online professional development and outcomes for students with disabilities - Frey, Timothy J. (My University, 2009)
Professional development experiences for special education teachers are designed to facilitate teacher learning and the implementation of evidence-based practices. Professional development should also make a positive impact on the K-12 students with disabilities that are in participating teachers’ classrooms. This study investigated the outcomes of the use of a project-based online professional development approach with in-service teachers of students with disabilities. In particular, the study focused on the effects of the professional development on K-12 students with disabilities in the participating teachers’ classrooms. The findings from the qualitative study indicate that each of the four student participants improved in the area of performance that was targeted by the teachers’ professional development. The analysis suggests that this approach to professional development positively impacted both participating teachers’ instructional practices and the performance of K-12 students with disabilities.
Keywords: Professional development; Online training; Special education; Collaborative learning communities